2019
DOI: 10.1101/750562
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural circuit mechanism underlying the feeding controlled by insula-central amygdala pathway

Abstract: SummaryCentral nucleus of amygdala (CeA) contains distinct populations of neurons that play opposing roles in feeding. The circuit mechanism of how CeA neurons process information sent from their upstream inputs to regulate feeding is still unclear. Here we show that activation of the neural pathway projecting from insular cortex neurons to CeA suppresses food intake. Surprisingly, we find that the inputs from insular cortex form excitatory connections with similar strength to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 75 publications
(77 reference statements)
1
8
0
Order By: Relevance
“…56 In mice, the IC-CeA pathway seems to be involved in carrying information about the aversive emotional state, inducing such behaviors as feeding suppression, place avoidance, and reducing exploration. 44,57,58 Our observation that inhibition of the AI-CeA pathway increased rearing is generally consistent with the literature. 58 What remains to be explained is why this projection seems to be preferentially recruited during the remote threat paradigm, which is otherwise characterized by active behavior (particularly rearing).…”
Section: Function and Molecular Identity Of Imminent Threat Versus Remote Threat Neuronssupporting
confidence: 91%
See 3 more Smart Citations
“…56 In mice, the IC-CeA pathway seems to be involved in carrying information about the aversive emotional state, inducing such behaviors as feeding suppression, place avoidance, and reducing exploration. 44,57,58 Our observation that inhibition of the AI-CeA pathway increased rearing is generally consistent with the literature. 58 What remains to be explained is why this projection seems to be preferentially recruited during the remote threat paradigm, which is otherwise characterized by active behavior (particularly rearing).…”
Section: Function and Molecular Identity Of Imminent Threat Versus Remote Threat Neuronssupporting
confidence: 91%
“…This observation is consistent with previous reports suggesting that the same CeA circuits can modulate intensity of different ongoing behaviors, depending on the current environmental context. 20,43,44 Because expression of the c-fos-dependent constructs used in this study can be evoked by any novelty in the environment, to control for their non-specific expression, i.e., unrelated to interaction with the demonstrators, we tested animals injected with the same constructs and exposed to similar conditions as the experimental groups except for the interaction with emotionally aroused partners. 26,45 Further, our preliminary data showed that expression of the constructs used here takes at least 2 h, and thus our optogenetic manipulations in the exploration and social interaction tests should not have led to stimulation of non-specific circuits.…”
Section: Function and Molecular Identity Of Imminent Threat Versus Remote Threat Neuronsmentioning
confidence: 99%
See 2 more Smart Citations
“…The conductance-based model with a dynamical system for the CeA neural network represents the biophysical interpretation of an excitable cell in regulating the feeding behaviour 75 . The intra-connections and projections modulate feeding behaviour in the CeA 36 where there are direct and indirect connections with different hypothalamic nuclei 52; 53; 76 .…”
Section: The Input/outputs Of the Central Amygdala And Their Modulatory Effects On Food Intakementioning
confidence: 99%